Defunct federalisms : critical perspectives on federal failure - Żółkoś, Magdalena; Kavalski, Emilian (Federalism studies., 2008)
This comparative volume looks at the track record of several defunct federalisms to identify options that have been overlooked and decisions that precipitated the collapse. Bringing together insights from the study of state failure and federal collapse, it examines the ways in which parallel assessment is crucial for suggesting the complex structures of identity accommodation in federal entities.